Implementation of occupancy grid-based mapping algorithm on ATRV-mini platform with Openwrt - dela Cruz, Divina Joy M.
Mapping and localization are fundamental in the operation of autonomous mobile robots. These require great processing power but enable the robot to navigate through its environment effectively. In this project, we implemented an occupancy grid-based mapping algorithm developed by Elfes and Maravec for the All-Terrain Robot Vehicle (ATRV), present in the Mobile Robotics Laboratory, on Linksys WRT54GL (WRT54GL) router. WRT54GL runs on Openwrt, a Linux-based firmware replacement. Ultrasonic sensors were used for ranging instruments. Electronic compass was also used to aid the robot in navigation. The algorithms was tested on various maze-type environments. Testing has shown that WRT54GL has enough memory and processing power to implement the mapping algorithm. Also, its wireless transmission capability allows efficient communication between the router and a host PC as compared to a wired connection. And the whole system was able to create a map of various maze-type environments.